FAKTOR-FAKTOR YANG MEMPENGARUHI PELAKSANAAN PROGRAM KELUARGA HARAPAN (PKH) BIDANG PENDIDIKAN DI DESA GUNUNG BUNGSU KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Yelinda Eka Putri; Nurhamlin ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research was conducted in Gunung Bungsu Village, XIII Koto Kampar District, Kampar Regency. The purpose of this study is (1) to find out the implementation of the Program Keluarga Harapan (PKH) of education sector.(2) and to determine the factors that influence the implementation of Program Keluarga Harapan (PKH). This study used a descriptive quantitative research method, totaling 128 people with a sample of 56 respondents selected by using simple random sampling technique. Based on the results of the study, it can be concluded that the implementation of Program Keluarga Harapan (PKH) in education sector is based on indicator data on the right target, right use and right amount are in good quality with a frequency of 56 respondents with a proportion of 100.0%. Communications factors that influence the implementation of Program Keluarga Harapan (PKH) in education sector based on indicators transmission are in good quality with a proportion of 73.2%. The clarity indicators are in good quality with a proportion of 100.0%. consistent indicators are in good quality with a proportion 69.6%. Based on the calculation results of the correlation test, it was found that the Pearson product moment value was 0.782, the probability number was 0.00. The correlation coefficient value was 0.782 which lies in the range 0.6 – 0.79(high. Keywords: Communication, The implementation of Program Keluarga Harapan (PKH